Syngas Production from CO2 Reforming of Methane Over Ceria Supported Cobalt Catalyst: Effects of Reactants Partial Pressure - Ayodele, Bamidele V.; Khan, Maksudur R.; Cheng, C. K. (Elsevier Ltd, 2015)
The production of syngas from CO2 (dry) reforming of methane is an environmental friendly process since it contributed to the mitigation of CH4 and CO2, the two principal components of greenhouse gases. In this study, ceria-supported cobalt catalyst was synthesized using wet-impregnation method and tested for the production of syngas from methane dry reforming. The main objective of this study is to investigate the effects of partial pressures of the reactants (CH4 and CO2) on the performance of the ceria-supported cobalt catalyst for syngas production via methane dry reforming. The CH4 and CO2 partial pressures were investigated within the range of 5–50 kPa at reaction temperatures of 923–1023 K in a fixed bed reactor at atmospheric pressure and gas hourly velocity of 30,000 h−1. The highest conversion of CH4 and CO2 were obtained to be 78 and 80% at CH4 partial pressure of 45 and 25 kPa respectively. Syngas ratio of 1.0 was produced at CH4 partial pressure of 40 kPa (reaction temperature of 1023 K)). The maximum yield of 40% and 38% were obtained for H2 and CO, respectively. The used catalyst was characterized by temperature programmed oxidation (TPO) for possible carbon deposition. The TPO analysis revealed the formation of graphitic carbon. The findings from this study show that syngas production from methane dry reforming over ceria-supported cobalt catalyst is significantly influenced by the variation in the partial pressure of the reactants.